2022
DOI: 10.1038/s41598-022-13199-w
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II variants defined by next generation sequencing are associated with sarcoidosis in Korean patients

Abstract: Polymorphic genes with immune functions, namely those of the human leukocyte antigen (HLA) system, have been implicated in sarcoidosis pathogenesis. As HLA polymorphisms in sarcoidosis have not been yet investigated in the Korean population, we used next-generation sequencing (NGS), allowing detailed characterization of HLA alleles to investigate the role of HLA variation in Korean sarcoidosis patients. We enrolled 103 patients diagnosed by the ATS/ERS/WASOG guidelines at Asan Medical Centre, Seoul, Korea. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…Observations of an association between sarcoidosis and HLA-DQB1*06:04 as a susceptibility and of HLA-DQA1*03:01 as a protective marker in the Czech population represent novel findings. Further, this study, including altogether 610 subjects, confirmed associations between HLA-DQB1*06:02 (susceptibility) and HLA-DRB1*01:01, HLA-DQB1*03:02 (protection), previously reported in smaller-scale studies in other, namely North-European and also East-Asian populations (13)(14)(15)(16)(17)…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Observations of an association between sarcoidosis and HLA-DQB1*06:04 as a susceptibility and of HLA-DQA1*03:01 as a protective marker in the Czech population represent novel findings. Further, this study, including altogether 610 subjects, confirmed associations between HLA-DQB1*06:02 (susceptibility) and HLA-DRB1*01:01, HLA-DQB1*03:02 (protection), previously reported in smaller-scale studies in other, namely North-European and also East-Asian populations (13)(14)(15)(16)(17)…”
Section: Discussionsupporting
confidence: 88%
“…Except for HLA-DRB1*01:01, which occurred more frequently in our Czech control population than in our patients, the other two protective variants were HLA-DQA1*03:01 and HLA-DQB1*03:02. HLA-DQB1*03:02 was recently reported as protective from sarcoidosis also in Korean population (13). HLA-DQA1*03:01 has so far never been mentioned in connection with sarcoidosis.…”
Section: Hla In Sarcoidosis Patients Compared With the Healthy Popula...mentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed interaction among viral infection, C*01 , is through the killer cell immunoglobulin‐like receptors of NK cells 28 . In this study, protection against AIN was observed for the allele C*03:04:01G , and the C*03:04 allele has previously been linked to sarcoidosis in Korean patients 29 …”
Section: Discussionmentioning
confidence: 49%
“…28 In this study, protection against AIN was observed for the allele C*03:04:01G, and the C*03:04 allele has previously been linked to sarcoidosis in Korean patients. 29 For HLA class II, we replicated all our previously published low-resolution findings of associated DRB1 alleles in this cohort of Danish AIN patients 5,12 and, at a G-group resolution, found the risk alleles to be DRB1*10:01:01G, DRB1*14:01:01G, DRB1*16:01:01G and the protective alleles to be DRB1*04:01:01G and DRB1*13:02:01G. For DQB1, we similarly replicated our previous findings for DQB1*03 and DQB1*05, and we found an association with DQB1*03:02:01G, DQB1*05:02:01G, and DQB1*05:03:01G.…”
Section: Discussionmentioning
confidence: 99%